Analysis Of Factors Affecting Wage Level Of Sri Pamela Hospital Employees High Cliff - Ben Setiawan; Diana Florenta Butar-Butar (International Journal of Artificial Intelligence Research, 2022)
This contemplate directs to influence how the psychoanalysis of constituents that consequence the commensurate of worker compensations at Sri Pamela Tebing Tinggi Hospital. The consequences showed that supported on the consequences of the psychoanalysis of possibility 1, it buoy be seen that the instruction changeable (X1) has no substantial chain reaction on the remuneration commensurate (Y). The consequences of this contemplate are not in occupation with preceding research, videlicet Muhammad Hafid 2018 psychoanalysis of constituents Influencing the remuneration commensurate of cloth manufacture working man in Pedurungan District, samarang municipality where the instruction changeable has no effect. supported on the consequences of the psychoanalysis of possibility 2, it buoy be seen that the acquaintance changeable (X2) has a cocksureness and substantial chain reaction on the remuneration commensurate (Y). The consequences of this contemplate are not in occupation with preceding research, videlicet Muhammad Hafid 2018 psychoanalysis of constituents impressive remuneration Levels for cloth manufacture working man in Pedurungan District, samarang municipality with elbow grease acquaintance variables having an consequence on remuneration levels. elbow grease (X3) has a cocksureness and substantial chain reaction on the remuneration commensurate (Y). The consequences of this contemplate are not in occupation with preceding research, videlicet Muhammad Hafid 2018 psychoanalysis of constituents impressive the remuneration commensurate of cloth manufacture working man in Pedurungan District, samarang City. With the expenditure of T enumeration is in a superior way than the over-the-counter variables